Design and development of a throwing frame equipment for cerebral palsy throwing sports - Fareen Nabilla Binti Zainuddin (School of Manufacturing Engineering, University Malaysia Perlis, 2016)
The purpose of this project is to study the design of sports equipment for cerebral palsy person. The target equipment that was found is the throwing frame. This throwing frame is specially designed for athlete that involved in throwing sports like javelin, discus throwi and shot-put. This throwing frame have disability sports classification from F32 until F34 that used to compete in sitting position. This class is divided depends on the level of disability. The probelms that are athlete faced when using this uquipment are it is very heavy, not portable and take a long time to install it. Thus, the objectives of this project are to design the lightweight and easily transported throwing frame as assist equipment for the athlete. Besides, to build the throwing frame that meet satisfy the Athletic Rule and Regulations is important aspects.